Android Based Animation Video Using Millealab Virtual Reality Application for Elementary School - Zulherman Zulherman; Galih Baskoro Aji; Supriansyah Supriansyah (Jurnal Pendidikan Indonesia, 2021)
Innovation in education is necessary for teachers and students to follow the learning process because of the limited laboratory facilities in elementary schools; science learning is done. This study aims to analyze student acceptance and understanding concept in using android-based animated videos on Millealab virtual reality in grade V elementary school. The research method process is carried out in several stages, starting from expert testing conducted on three media experts, three subject matter experts, and three teachers from 3 different schools. Test the use of virtual reality video with a sample size of 65 students. Collecting data using a Likert scale questionnaire 1 to 5, and treatment in descriptive analysis. Testing the acceptance of virtual reality videos to students showed that students received virtual reality video media during the learning process. The application of virtual reality (VR) technology in science learning in elementary schools can improve conceptual understanding so that student acceptance of VR is excellent and teachers also feel helped by using VR media to support the learning process. VR technology is better than AR because it is more comprehensive and easier to use by teachers and students.